Diffraction on heavy samples at STRESS-SPEC using a robot system. Issue 1 (April 2015) - Al-Hamdany, N; Gan, W M; Randau, C; Brokmeier, H-G; Hofmann, M
Abstract: The material science diffractometer STRESS-SPEC has high flux and a high flexible monochromator arrangement to optimize the needed wavelength. Many specific sample handling stages and sample environments are available. One of them is a Staubli RX 160 robot with nominal load capacity of 20 kg and more freedom for texture mapping than the Huber 512 Eulerian type cradle. Demonstration experiments of non-destructive pole figures and strain measurements of Cu-tube segments weighing 12 kg weight and 250 mm in length and 140 mm diameter have been carried out. The residual strains measured by the robot and by the XYZ- stage fit quite well, that means the robot is reliable for strain measurements. The texture of the Cu-tube has dominant recrystallization texture components represented by the cube and the rotated cube.